Efek Tekanan Pekerjaan Terhadap Stres Kerja Serta Implikasinya Pada Keinginan Untuk Pindah Pada Karyawan - Randhy Vico Bramasta; Survival Survival; Adya Hermawati (Universitas 45 Surabaya, 2023)
The research objective was to determine the effect of job pressure on work stress and the implications for intention turnover at PT. Woori Finance Indonesia Malang City. The approach used is a quantitative approach and the type of research used is explanatory research. The population is all employees, totaling 37 employees. The sampling technique in this study was carried out by the total sampling method. The statistical data analysis technique through path analysis used in this study is Partial Least Square-Structural Equation Modeling (PLS-SEM) with the SmartPLS application. The results showed that work pressure has an effect on work stress. Work stress has no effect on intention turnover. Job pressure effect on intention turnover. Job pressure has no effect on intention turnover mediated by work stress.